Atypical forms of employment in the public sector: Are there any? - Berndt Keller; Hartmut Seifert (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The paper deals with various forms of atypical employment in the public sector that are widely neglected in existing research; its specific focus is on their development, scope, distribution and structural features. In the first part we break down the purely statistical category and differentiate between the disparate forms (part-time, marginal employment or minijobs, midijobs, fixed-term, agency work). In the second part we address the question if these forms are not only atypical, but also have to be classified as precarious. We distinguish various risks operative in the short, medium and long term (income, stability of employment and employability, pensions). Finally, we differentiate between employment in the private as well as the public sector and draw parallels and indicate specific differences in their development and situation. Our basic finding is that atypical forms of employment are also widespread in the public sector but are all in all less precarious than in the private sector. The distribution of individual forms shows major differences between both sectors whereas the overall percentages are similar.
Keywords: 330